Negociações comerciais internacionais e democracia o Brasil nos contenciosos da OMC na era FHC (1995-2002) - Oliveira, Marcelo Fernandes de (Editora Oficina Universitária, 2022)
"INTERNATIONAL TRADE NEGOTIATIONS AND DEMOCRACY" addresses a highly relevant topic for International Relations in Brazil, but also for the sectors of legislative formulation and execution of public policies. Starting from a classic question of Brazilian Foreign Policy - the thesis of the bureaucratic insulation of the Ministry of Foreign Affairs -, prof. Marcelo F. de Oliveira focuses on the new conditions under which the country's international trade negotiations began to take place in governments led by the PSDB (1995-2002). To carry out this task, the author dialogues with liberal theories of International Relations and finds, in the Two-Level Game model, the theoretical basis for interpreting the bargaining moves, tactical and strategic, carried out by Brazil and its interlocutors. During the governments of Fernando Henrique Cardoso, the negotiations took place in a context that brought news: redemocratization and the impulse of globalization. In this new era, on the one hand, the participation of the Brazilian Congress should become more relevant for Brazil's International Relations, since much of the credibility regarding the internalization of international commitments is now decided by the Legislature. On the other hand, the author analyzes that not all themes of international trade or negotiations that arouse the interest of parliamentarians, and assesses how this impacts the ability of the Presidency and Itamaraty to forward negotiations, even those that take place in more institutionalized environments, such as the Dispute Settlement Body of the World Trade Organization (WTO). These reflections are supported by a detailed study of three disputes - pharmaceutical patents, cotton and sugar - fought within the scope of the WTO, the first two against the United States and the third against the European Union. The cases, in addition to encouraging theoretical reflection, bring important empirical records of these paradigmatic negotiations for Brazil and for the international literature. In short, 'International Trade Negotiations and Democracy' is a fundamental work for understanding the country's negotiating capacity in a democratic and globalization context. The book sheds light on complex formulation processes and decision dynamics that foreign negotiators must consider in their dealings with Brazil and which, therefore, Brazilian negotiators themselves cannot ignore.